Radiation exposure from videofluoroscopic swallow studies in children with a type 1 laryngeal cleft and pharyngeal dysphagia: A retrospective review. (October 2016) - Hersh, Cheryl; Wentland, Carissa; Sally, Sarah; de Stadler, Marie; Hardy, Steven; Fracchia, M. Shannon; Liu, Bob; Hartnick, Christopher
Abstract: Introduction: Radiation exposure is recognized as having long term consequences, resulting in increased risks over the lifetime. Children, in particular, have a projected lifetime risk of cancer, which should be reduced if within our capacity. The objective of this study is to quantify the amount of ionizing radiation in care for children being treated for aspiration secondary to a type 1 laryngeal cleft. With this baseline data, strategies can be developed to create best practice pathways to maintain quality of care while minimizing radiation exposure. Methods: Retrospective review of 78 children seen in a tertiary pediatric aerodigestive center over a 5 year period from 2008 to 2013 for management of a type 1 laryngeal cleft. The number of videofluoroscopic swallow studies (VFSS) per child was quantified, as was the mean effective dose of radiation exposure. The 78 children reviewed were of mean age 19.9 mo (range 4 mo–12 years). All children were evaluated at the aerodigestive center with clinical symptomatology and subsequent diagnosis of a type 1 laryngeal cleft. Aspiration was assessed via VFSS and exposure data collected. Imaging exams where dose parameters were not available were excluded. Results: The mean number of VFSS each child received during the total course of treatment was 3.24 studies (range 1–10). The average effective radiation dose per pediatric VFSS was 0.16 mSv (range: 0.03 mSv–0.59 mSv) per study. Clinical significance was determined by comparison to a pediatric CXR. At our facility a CXR yields an effective radiation dose of 0.017 mSv. Therefore, a patient receives an equivalent total of 30.6 CXR over the course of management. Conclusions: Radiation exposure has known detrimental effects particularly in pediatric patients. The total ionizing radiation from VFSS exams over the course of management of aspiration has heretofore not been reported in peer reviewed literature. With this study's data in mind, future developments are indicated to create innovative clinical pathways and limit radiation exposure.